Superfoods and their impact on brain health: a systematic review - Raghupathi Niranjan Kumar; Haja Nazeer Ahamed (Discover Food)
Abstract Aim of the study This review examines the pharmacology and clinical applications of superfoods like Crocus sativus, Murraya koenigii, Phoenix dactylifera, Punica granatum, Ficus carica, and Beta vulgaris on mental health, anxiety, depression, schizophrenia, Alzheimer's disease, cognitive decline, psychosis, Parkinson's disease, and stroke. We hope this perspective guides superfood research. Materials and methods We used PRISMA for our systematic review. We used Google Scholar, PubMed, ProQuest, ResearchGate, and Springer Link. Other book chapters are investigated in this study. We chose 95 original research articles for the study after identification, exclusion, eligibility, and inclusion. Results Crocus sativus had 150 glycosides, carotenoids, flavonoids, monoterpenes, and derivatives that were reviewed. These drugs may assist depression, anxiety, Alzheimer's, schizophrenia, Parkinson's, stroke, memory, and cognition. Murraya koenigii boosts brain-protecting glutathione peroxidase and SOD. These antioxidants are abundant: linalool, terpinene, myrcene, murrayanol, alpha-pinene Murraya koenigii extract enhances cholinergic transmission and reduces serotonergic and dopaminergic transmission. The anthocyanins, tannins, flavonoids, phenolic acids, and lignans in Punica granatum polyphenols reduce depression, anxiety, memory loss, and oxidative also decrease stroke. Beta vulgaris antioxidants, betanin, and nitrates prevent oxidation. Phoenix dactylifera and Ficus carica polyphenols reduce anxiety, depression, Alzheimer's, antioxidants, and stroke. Ficus carica, Punica granatum, and Phoenix dactylifera antioxidants inhibit cerebral ischaemia. Conclusion After reviewing 95 papers, Ficus carica, Crocus sativus, Beta vulgaris, Murraya koenigii, Punica granatum, and Phoenix dactylifera are neuroprotective and therapeutic. Flavonoids in Ficus carica reduce anxiety and depression, whereas Punica granatum improves memory. Phoenix dactylifera are antioxidants, Beta vulgaris decreases anxiety and depression. They need more research to verify their long-term efficacy.